Prevalence and Environmental Contamination of Soil-Transmitted Helminths Among School-Aged Children in Abia State University Staff School Uturu, Nigeria - Obisike, Victor Ugochukwu; Dike, Maduabuchi Chizuruoke; Ukpai, Ukiwe Favour (European Journal of Applied Sciences, 2025)
Soil-transmitted helminths (STH) remain a significant public health concern in developing countries, particularly among school-aged children who are highly susceptible due to frequent exposure to contaminated environments and poor hygiene practices. This study aimed to determine the prevalence of STH infections among pupils of Abia State University Staff School and assess environmental contamination with helminth eggs. A total of 75 stool samples were collected from pupils whose parents consented to the study. Additionally, soil samples were collected in triplicates from the playground, near the toilet area, and close to the dumpsite. Stool samples were processed using the Kato-Katz technique, while soil samples were examined for helminth eggs following the standard methods and identified morphologically. Results showed that 62.7% of the examined pupils were infected with at least one helminth species. Taenia spp was the most prevalent (21.3%), followed by Ancylostoma duodenale (18.7%), Trichuris trichiura (12.0%), and Ascaris lumbricoides (10.7%). Males had a slightly higher infection rate (38.7%) compared to females (26.7%). Infection was more common in younger children, particularly those in Basic One and Basic Two. Soil analysis revealed helminth egg contamination in all sampled environments, with the highest prevalence near the toilet area (32.0%). These findings underscore the need for improved sanitation, regular deworming, and health education programs to reduce STH transmission. Targeted interventions should focus on younger children, given their higher vulnerability to infection.